Perceraian, Aktor, Modal Pendidikan, dan Ekonomi dalam Masyarakat Indramayu - Elis Sahmiatik; Subaidi Subaidi (Jurnal Ilmiah Wahana Pendidikan, 2022)
The Corona widow phenomenon popular during the Covid-19 pandemic, with divorce cases dominated by divorce from women or khuluk. This phenomenon is the basis for making this article, by offering three problem formulations, (1) how are the problems of divorce in Indramayu Regency? (b) why is the role of women important to improve the quality of marriage? (3) what is the relevance of the prospective bride and groom to the high divorce rate in KUA Lohbener, Indramayu?. This article is a case study with a qualitative descriptive research method. Data were collected by means of participant observation, interviews, and documentation. The process of data analysis is carried out by collecting data in the literature and the results of direct field observations. The results of this article show the understanding of the concept of marriage and the role of women which is highlighted because the phenomenon of divorce that occurs in the Indramayu area is a dominated by divorce lawsuits or khuluk propased by women and the highest factor of divorce in Indramayu is the economy.